Application of C14/SiO2–Fe3O4 and AC–Fe3O4 nanocomposite for U(VI) removal. Issue 47 (7th October 2016) - Akbari-Jonoush, Zohreh; Naseri, Simin; Farzadkia, Mahdi; Mohajerani, Hamid-Reza; Shirzad-Siboni, Mehdi; Yang, Jae-Kyu
Abstract: In this study, C14 /SiO2 –Fe3 O4 and AC–Fe3 O4 nanocomposite synthesized by co-precipitation method were used as adsorbents for the removal of U(VI) from aqueous solutions. The main compositions of AC–Fe3 O4 and C14 /SiO2 –Fe3 O4 were characterized by Fourier transform infrared spectroscopy, X-ray diffraction, and scanning electron microscopy. The removal efficiency of U(VI) was studied as a function of pH, contact time, ionic strength, temperature, adsorbent dose, initial U(VI) concentration, and initial benzamide concentration. Maximum adsorption of U(VI) was obtained at pH 6. The removal of U(VI) reached an equilibrium within 30 min by C14 /SiO2 –Fe3 O4 and 90 min by AC–Fe3 O4, respectively. Removal efficiency of U(VI) by both adsorbents was decreased with increasing ionic strength and initial U(VI) concentration, but was increased with increasing temperature and adsorbent dosage. Kinetic study revealed that the pseudo-second order model well described the adsorption of U(VI) onto two adsorbents. When adsorption data was analyzed by both Langmuir and Freundlich adsorption isotherms, it was better described by the Langmuir model. The maximum adsorption of U(VI) was 16.29 and 15.87 mg/g by C14 /SiO2 –Fe3 O4 and AC–Fe3 O4 nanocomposite, respectively. The thermodynamic parameters of the adsorption process indicated that adsorption occurred through endothermic process. Overall, this work shows that C14 /SiO2 –Fe3 O4 is a more effective adsorbent than AC–Fe3 O4 for the removal of low concentration of U(VI).